Time and space in the internet age - Kern, Stephen, author.
1 online resource.
Keywords: "This book analyzes changes in ideas about and experiences of time and space from 1880 to 2020, relying on new technologies for causal explanations of changes in nine key elements of time and space. Time and Space in the Internet Age is a thought-provoking study for academics and general readers interested in the history of technology and science"--